USING STATISTICAL ANALYSIS AND EXPLANATORY POWER IN TWO APPROACHES TO EATING DISORDER PROBLEMS - Mahmoudiyan, Tahereh; Badkoobehi, Hassan (LIFE: International Journal of Health and Life-Sciences, 2020)
This study compares the effectiveness of schema therapy and cognitive behavioral therapy (CBT) on modifying early maladaptive schemas in patients with bulimia nervosa considering parental bonding and examining the relative roles of statistical analysis and explanatory power. The study follows an experimental methodology with pretest-posttest design and follow-up with control group. The population for the study includes all patients aged 16 to 23 years with eating disorders who had been referred to psychiatry, psychotherapy, and obesity clinical treatment centers in Tehran. Purposive sampling was used in this study. 39 patients were diagnosed to have Bulimia nervosa by performing psychological screening. Finally, the selected patients were matched in two experimental groups and one control group. Data were collected through two questionnaires and diagnostic interviews based on diagnostic criteria for eating disorders and psychiatric diagnosis. The two questionnaires used in the study included: (1) Parental Bonding Questionnaire (2) Young Schema Questionnaire. The main problems of the patients included having cuts, being rejected, autonomy, and impaired performance. However, they were less vulnerable in other areas including orientation and violating restrictions. The findings of this study can be helpful in the etiology of bulimia nervosa disorder based on the systematic approach and pave the way for further research in this area.